Kajian Hubungan Nilai Void terhadap Umur Rencana Perkerasan Jalan pada Campuran AC-WC dengan Variasi Perendaman Mengggunakan Air Hujan (JURNAL RISET RUMPUN ILMU TEKNIK, 2026)
The performance of Asphalt Concrete – Wearing Course (AC-WC) is greatly influenced by the characteristics of the mixture, one of which is the void value which plays a role in stability, durability, and resistance to damage. Rainwater is the most dominant environmental factor accelerating pavement damage through stripping mechanisms, bond release, and a decrease in the structural strength of the layer. Therefore, it is necessary to conduct a study on changes in void value with soaking duration, the relationship of void value to the design life of the road pavement, and an empirical model of the design life based on void value with variations in soaking in the mixture using a laboratory test approach. Based on the results of laboratory tests, it can be seen that changes in void values ​​due to variations in soaking time using rainwater indicate that the longer the mixture is soaked, the changes in VIM and VMA values ​​tend to decrease, while VFA increases. The relationship between VIM values ​​and the design life of road pavements in AC-WC layers due to soaking variations shows that the design life decreases sharply when the VIM value is <3%. Thus, long-term immersion can reduce the road life by more than 35% of its ideal design life and based on a simple empirical model equation to estimate the design life of the pavement based on the void value and immersion conditions, N0 = 12.5 years is obtained (Ideal mix design life at VIM = 4%).